The children's film festival [videorecordings] - Heartshaper Video (Philippines : Lighthouse Educational Corp., 2008)
A collection of short films designed for children that present entertaining stories with positive values and Christian themes. Through engaging characters and simple storytelling, the films encourage young viewers to learn important lessons about kindness, faith, honesty, and making good choices in everyday life.
Children.
Keywords: Christian life $1 (BJuvenile films.s -- Moral education $1 (BJuvenile films.s -- Children$1 (Bs stories $1 (BFilm adaptations.s -- Values $1 (BJuvenile films.s